Islam Inklusif di Sekolah Umum: Studi tentang Toleransi dan Interaksi antaragama di SMA Negeri 2 Tuban - Hasanah, Asma Hidayatul; Nisa, Lathifatun; Achoita, Ana (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the implementation of inclusive values in fostering interreligious tolerance at SMA Negeri 2 Tuban. The method used is qualitative with a case study design. Data were obtained through observation, in-depth interviews, and documentation, then analyzed using data reduction, presentation, and conclusion drawing techniques. The results indicate that inclusive values are applied through a school culture that respects diversity, the integration of tolerance values in learning activities and student organizations, as well as the teachers' exemplary behavior in interacting across faiths. The implementation of these inclusive values positively impacts the formation of harmonious and respectful social relationships among students from various religious backgrounds. This condition creates a peaceful and safe school environment for all parties. The study emphasizes that inclusive education plays a strategic role in building a school ecosystem that is not only adaptive to diversity but also civilized by prioritizing humanitarian values and respect for differences as the main foundation for a harmonious and sustainable society. This research confirms that inclusive education plays a strategic role in building a peaceful, adaptive, and civilized school ecosystem.